Functional characterisation of ADIPOQ variants using individuals recruited by genotype. (15th June 2016) - Lee, Benjamin P.; Lloyd-Laney, Henry O.; Locke, Jonathan M.; McCulloch, Laura J.; Knight, Bridget; Yaghootkar, Hanieh; Cory, Giles; Kos, Katarina; Frayling, Timothy M.; Harries, Lorna W.
Abstract: Four non-coding GWAS variants in or near the ADIPOQ gene (rs17300539, rs17366653, rs3821799 and rs56354395) together explain 4% of the variation in circulating adiponectin. The functional basis for this is unknown. We tested the effect of these variants on ADIPOQ transcription, splicing and stability respectively in adipose tissue samples from participants recruited by rs17366653 genotype. Transcripts carrying rs17300539 demonstrated a 17% increase in expression (p = 0.001). Variant rs17366653 was associated with disruption of ADIPOQ splicing leading to a 7 fold increase in levels of a non-functional transcript (p = 0.002). Transcripts carrying rs56354395 demonstrated a 59% decrease in expression (p = <0.0001). No effects of rs3821799 genotype on expression was observed. Association between variation in the ADIPOQ gene and serum adiponectin may arise from effects on mRNA transcription, splicing or stability. These studies illustrate the utility of recruit-by-genotype studies in relevant human tissues in functional interpretation of GWAS signals. Highlights: Genetic variants in the ADIPOQ gene associate with variation in adiponectin levels. Transcripts carrying rs17300539 demonstrate 17% increased expression. Transcripts carrying rs17366653 demonstrate altered splicing. Transcripts carrying rs56354395 demonstrate 59% increased expression. These variants may act by altering ADIPOQ mRNA transcription, splicing or stability.